INSTRUCTOR TRAINING MANAGEMENT FOR EDUCATION AND TRAINING UPGRADING OF SEAFARER COMPETENCY PROGRAMME LEVEL IV AT POLITEKNIK PELAYARAN MALAHAYATI - Rahmat Kurnia; Cut Zahriati Harun; Yusrizal Yusrizal (Berajah Journal, 2023)
This research aims to determine the planning, implementation, evaluating and obstacles of Instructor Training to Improve seafarers at Level IV at Politeknik Pelayaran Malahayati. The approach used in this research was a qualitative approach. The type of research used in this research was descriptive. The instruments used in this study consisted of interview sheets and observation guidelines. The implementation of the program uses the online method for distance learning, this method is used when participants are on board and even abroad. Practical learning using laboratories, simulators and training ships, the criteria for instructors who teach must have a level III training certificate and have sailed for two years. The training material follows the sailor curriculum that has been prepared by BPSDM and approved by the ministry of sea transportation. Evaluation is carried out systematically starting with evaluating student attendance, material achievement, and conducting exams. The exam results will be communicated to the management after which the management will provide follow-up on the evaluation results. Those who carry out the evaluation are all management parties in their respective fields. Barriers are generally divided into two, namely internal and external barriers to the program. Barriers from within are technical where there is often a decrease in electrical power so that it can interfere with the activities of electrical devices. While external obstacles as a whole did not interfere with the running of the program.